The Effect of Sleep Quality On The Grade Point Average of Medical Students At Prima Indonesia University Class of 2023 - Yudhisthira Sakthi; Primta Bangun; Alvin Abrar Harahap (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Medical students are exposed to high academic demands, which often lead to poor sleep quality and may impact cognitive function and academic achievement. This study aimed to analyze the relationship between sleep quality and grade point average (GPA) among medical students at Prima Indonesia University, class of 2023. Methods: A quantitative analytic approach with a cross-sectional design was used. The population included all active students from the 2023 cohort, with 162 respondents selected by simple random sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), and GPA data were obtained from official academic records. Data analysis involved univariate and bivariate statistics, with normality tested using Kolmogorov–Smirnov and correlation assessed by Spearman's rank test. Results: The majority of students (63.6%) had poor sleep quality (PSQI > 5), and the average GPA was 3.29. Spearman analysis showed a moderate negative correlation (rₛ = –0.505, p < 0.05) between sleep quality and GPA, indicating that poorer sleep quality was associated with lower academic achievement. Conclusion: Poor sleep quality significantly affects academic performance in medical students, highlighting the need for sleep hygiene education and time management interventions.